The Process of Adaptation and Assimilation Beyond 1957 As Remembered by the Descendants of the Czech Brethren in the Lower Silesia - Maciej Zawistowski (Sprawy Narodowościowe. Seria nowa)
Based on nine independently conducted oral history interviews, in this article I analyze the process of adaptation and assimilation of the descendants of the Czech Brethren in the area of Strzelin (formerly German Strehlen) in Lower Silesia between 1957 and 1989. The main objective is to answer the question how the descendants portray and value the process of assimilation into the new social reality after 1956 in their biographical narratives. First, I briefly present the state of the community in 1957 and outline the reasons why some of its members decided to remain in Lower Silesia. Then, I describe the various dimensions of how community members functioned during the period of People’s Poland: firstly, in a minority organization, the Social and Cultural Association of Czechs and Slovaks, and, secondly, in the parish community of the Evangelical Reformed Church, as well as in mixed families and the local community. The presented research contributes to the understanding of the dynamics of family, neighborhood and local government relations in a post-displacement region. The study adopts the approach known as rescue history (historia ratownicza) at the level of microhistory.